My honey bear book of rhymes - Taylor, Dorothy; Taylor, John, 1937-; Price-Thomas, Brian (New York, N.Y. : Modern Publishing, 1985)
A collection of twenty-eight traditional nursery rhymes and songs accompanied by full page illustrations.
Keywords: Nursery rhymes; Children's poetry; Nursery rhymes